12th International Conference “Environmental Engineering” (ICEE-2023) - Čygas, Donatas; Vaiškūnaitė, Rasa (International Conference “Environmental Engineering”, 2023)
Lietuvos mokslų akademija / Lithuanian Academy of Sciences